2010
DOI: 10.1039/c0nr00420k
|View full text |Cite
|
Sign up to set email alerts
|

Control of morphology and nanostructure of copper and cobalt oxalates: Effect of complexing ions, polymeric additives and molecular weight

Abstract: Precipitated oxalates are often nanostructured and can be used as precursors for nanostructured oxides for different applications. The modification of the particle shape and nanostructures of both copper and cobalt oxalates has been demonstrated using polymeric additives or complexing counter-ions. In the case of cobalt oxalate the characteristic elongated rod particle shape (axial ratio of 10) can be modified by using polymethymethacrylate (PMMA) to produce particles with lower axial ratios of 2, through cube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
12
0
3
Order By: Relevance
“…Slower ramp -up rate led to better catalytic activity. By examining the catalyst and deposited carbon after the reaction using TEM, it was revealed that the self-regulating system allowed the formation of active from the hydrogen bonds between the ribbons due to the H 2 O molecules [193,194].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slower ramp -up rate led to better catalytic activity. By examining the catalyst and deposited carbon after the reaction using TEM, it was revealed that the self-regulating system allowed the formation of active from the hydrogen bonds between the ribbons due to the H 2 O molecules [193,194].…”
Section: Discussionmentioning
confidence: 99%
“…5.2 (a) inset) revealed that one particle was actually composed of bundles of nano-wires which were stacked in a parallel between the ribbons due to the H 2 O molecules as shown in Fig. 5.3 [193,194]. Every nickel ion was bonded by two C 2 O 4 ions to form a planar molecule in the complexes.…”
Section: Effect Of Reactant Concentrationmentioning
confidence: 97%
“…Wisgerhof és munkatársai bizonyították röntgendiffrakciós mérésekkel, hogy szobahőmérsékleten az oxálsav és a kobalt-klorid vizes közegű egyszerű oldatreakciója segítségével előállítható a termodinamikailag kevésbé stabil, halvány szürkés CoC 2 O 4 · 4H 2 O kristályvizes forma [115,116]. A kobalt-és réz(II)-oxalátok legfontosabb ipari felhasználása, hogy prekurzor vegyületei az átmenetifém-oxidoknak [117]. E két átmenetifémionnak a sugara hasonló méretű, így képesek szilárd oldat képzésre, vagyis képesek egymás helyettesítésére a kristályrácsban mint például Co 0,7 Cu 0,3 C 2 O 4 · 2H 2 O [118], mely röntgendiffraktometriás analízissel könnyen megkülönböztethető a két oxalát szilárd keverékétől [119].…”
Section: áTmenetifém-oxalátok Előfordulása éS Alkalmazásaunclassified
“…Az irodalomban a kobalt(II)-oxalát vizes közegben történő morfológiát befolyásoló anyagoktól mentes szintézise során a pálca morfológia a jellemző mind a dihid-rát, mind a tetrahidrát kristályvizes formát tekintve. A kristályok mérete pedig az előállítási módszertől függően mikrométer és mikrométer alatti hosszal jellemezhető [104,115,117]. A jól kevert referencia rendszer esetén térbeli koncentrációgradiens nem lép fel és a 41.…”
Section: A Csapadék öSszetétele éS Szerkezeti Tulajdonságaiunclassified
See 1 more Smart Citation